Determination of insoluble calcium content in Cheddar, feta, Juustoleipa, and mozzarella cheeses using acid-base buffering curves - Rachel Lindstrom; Prateek Sharma (JDS Communications)
The amount of colloidal calcium phosphate (CCP) complex associated with caseins (insoluble [INSOL] Ca) determines the body, texture, flavor, and breakdown of cheese constituents during aging. The continuous pH decline during cheesemaking because of lactic acid fermentation results in solubilization of INSOL Ca. Measuring INSOL Ca in such a dynamic and wide range pH system (6.6 to 5.3) is challenging. The purpose of this study was to test utility of an acid-base auto-titration method in differentiating INSOL Ca content in cheeses with a wide range of pH (i.e., Juustoleipa 6.6, mozzarella 5.6, Cheddar 5.3, feta 4.8) and also to understand the relationship between pH, protein content, and INSOL Ca. A positive relationship was obtained for pH (R2 = 0.62) and protein content (R2 = 0.85) with INSOL Ca, suggesting concomitant release of CCP content at lower pH values and association of higher amount of CCP with higher protein content. Despite having a pH slightly closer to mozzarella (pH 5.56), Cheddar cheese (pH 5.25) had more INSOL Ca (0.67%) owing to the highest amount of protein (26%) and low moisture content (33%). Feta had the lowest amount of INSOL Ca (0.15%) owing to a low pH (4.79), higher moisture content (55%), and low protein content (14%). Juustoleipa had the highest percentage of INSOL Ca out of total Ca (88%) due to higher pH (6.62) and more intact casein. It was evident that the acid-base titration method was able to differentiate INSOL Ca between different types of cheeses with varying pH and protein content. Findings of this work will help tracking the proportion of INSOL Ca at various stages of cheesemaking and understanding kinetics of INSOL Ca solubilization and its role in causing pH variation in the early stage of cheese ripening.